Muscle strength exercises to improve performance in baseball hitters (Original) (Revista científica Olimpia, 2020)
This article refers to the results obtained in fast force training and plyometrics in Baseball batters from the Campechuela municipality, belonging to the Granma province. The objective of this research is based on achieving an increase in offensive performance, which translates into having strong, fast and explosive muscles, in order to achieve improvement in joint mobility, coordination of movements, fluidity and harmony in the technical gesture, and thereby achieve the conformation of an excellent physical condition. The population that was used counted with the participation of 12 batters, led by specialists and technicians who are dedicated to teaching and perfecting this sport, those who maintain a constant concern, direct their efforts to the preparation of this capacity in batters.  With the application of these exercises, it was possible to increase muscle strength indexes with an emphasis on fast strength and plyometry in baseball batters of the first category, in addition to achieving, after 21 years, winning the gold medal in the 2020 provincial championship.
Keywords: hitters; baseball; exercice; fast force; plyometry